Bio-softening of Coir Yarn for Ecofriendly Wet Processing - Ravindranath, Anita Das; Chitralekha, M. (International Coconut Community Journal, 2010)
Conventional chemical bleaching of coir generates a considerable amount of effluent which is discharged into the local water bodies thereby affecting the water quality there. The possibility of bio-bleaching and bio-softening of coir yarn in order to reduce the requirement of softening and bleaching chemicals in wet processing of coir was studied. Treatment of coir yarn for 72 hrs using Trametes versicolor (NCIM 993) and Coirret, a bacterial consortium was carried out. The bio-treatment could impart an appreciable degree of softness to the yarn which was confirmed by the Flexural Rigidity Test. An improvement in softness of the yarn to the extent of 38% using bacterial treatment and 46% using fungal treatment was achieved. A noticeable change was observed in surface morphology of the fibre through SEM analysis. The lignin content of the fungal treated yarn was also reduced to some extent. An increase of 10% in Brightness Index of the fungi treated yarn was observed and a reduction in the requirement of bleaching chemicals could also be achieved. The physico-chemical parameters of the residual bleach liquor were also studied and a considerable decrease in BOD, COD and phenol content was observed.